Measuring Quality of Life in Female Genital Cosmetic Procedure Patients: A Systematic Review of Patient-Reported Outcome Measures. (13th November 2019) - Sharp, Gemma; Maynard, Pascale; Hamori, Christine A; Oates, Jayson; Sarwer, David B; Kulkarni, Jayashri
Abstract: Background: In the subspecialty of female genital cosmetic procedures, patient satisfaction and quality of life are key outcome measures. As such, valid and reliable patient-reported outcome measures (PROMs) examining these outcomes are essential. Objectives: The authors sought to identify and scrutinize all PROMs developed for female patients undergoing genital cosmetic procedures. Methods: The authors performed a systematic literature review utilizing MEDLINE, PreMEDLINE, Ebase, Embase, OVID, CINAHL, Cochrane Library, PsycINFO, PubMed, and Google Scholar to identify PROMs developed and validated for utilization in female genital cosmetic procedure patients. Instruments identified were assessed according to international guidelines for health outcome measures development and validation. Results: The authors identified 50 outcome questionnaires employed in the female genital cosmetic procedure literature. Of these, 26 were ad hoc instruments (ie, had not been formally developed and tested) and 22 were generic instruments (ie, intended for use in broad groups of people, not only specific patient groups). Only 2 instruments have been validated in a female genital cosmetic procedure patient population. These were the Genital Appearance Satisfaction scale and the Cosmetic Procedure Screening Scale–Labiaplasty. Although both these scales had undergone fairly rigorous psychometric development and validation, both had content limitations. Conclusions: There is a lack of specific, valid, and reliable satisfaction and quality-of-life PROMs in the field of female genital cosmetic procedures. Future research should involve the development of such measures to more accurately assess the outcomes and benefits of these procedures.